PENDAMPINGAN DARING SUPERVISI AKADEMIK KEPALA MADRASAH DI MASA PANDEMI COVID-19 - Eni Rindarti (Balai Diklat Keagamaan Jakarta, 2021)
Abstract This action research aims to improve the academic supervision competency of madrasa principals through technical guidance during the Covid-19 pandemic. The research was carried out in January s.d. May 2021. The Action Research involved four heads of Madrasah Aliyah in Central Jakarta as participants, researchers as mentors, and three observers. Research data were collected through observation, interviews, tests, filling out questionnaires, and document assessment. The research data were analyzed through data reduction, data presentation, and verification, accompanied by a description of quantitative data on test results, process assessment, and document assessment. Actions are carried out in two cycles. The results of observations showed an increase in online mentoring participation from 75% in the first cycle to 87.5% in the second cycle; there was an increase in the ability of madrasah principals in preparing academic supervision from 72% in the first cycle to 92.5% in the second cycle; the increase in knowledge about academic supervision increased from 73.25 before the action to 83 after the action, and improvement in the ability of the head of madrasah to prepare reports on academic supervision reached a score of 92.5%% at the end of the activity. Based on this research, it can be concluded that online technical guidance during the Covid-19 pandemic can improve the ability of madrasa principals to carry out academic supervision. Abstrak Penelitian Tindakan ini bertujuan meningkatkan kemampuan kepala madrasah melaksanakan supervisi akademik pada masa pandemi Covid-19 melalui pendampingan daring. Penelitian dilaksanakan pada bulan Januari s.d. Mei 2021. Penelitian Tindakan melibatkan empat kepala Madrasah Aliyah di Kota Jakarta Pusat sebagai peserta pendampingan, peneliti sebagai pendamping, dan tiga observer. Data penelitian dikumpulkan melalui observasi, wawancara, tes, pengisian kuesioner, serta penilaian dokumen. Data penelitian dianalisis melalui reduksi data, penyajian data, dan verifikasi, dilengkapi deskripsi data kuantitatif hasil tes, penilaian proses, dan penilaian dokumen. Tindakan dalam bentuk pendampingan daring dilaksanakan dalam dua siklus. Hasil observasi menunjukkan peningkatan pertisipasi pendampingan daring dari 75% pada siklus-I menjadi 87,5% pada siklus-II; terjadi peningkatan kemampuan kepala madrasah dalam menyusun program supervisi akademik dari 72% pada siklus-I menjadi 92,5% pada siklus-II; kemampuan kepala madrasah menyusun laporan supervisi akademik mencapai skor 92,5%% di akhir kegiatan, dan peningkatan pengetahuan tentang supervisi akademik meningkat dari 73,25 sebelum tindakan menjadi 83 setelah tindakan. Berdasarkan penelitian ini dapat disimpulkan bahwa pendampingan daring pada masa pandemi Covid-19 dapa meningkatkan kemampuan kepala madrasah dalam melaksanakan supervisi akademik.